The Role of m6A Epigenetic Modification in the Treatment of Colorectal Cancer Immune Checkpoint Inhibitors - Tong, Huan; Wei, He; Smith, Alhaji Osman; Huang, Juan (Frontiers in Immunology, 2022)
Tumor immunotherapy, one of effient therapies in cancers, has been called to the scientific community’s increasing attention lately. Among them, immune checkpoint inhibitors, providing entirely new modalities to treat cancer by leveraging the patient’s immune system, have quickly become the first-line treatment for varieties of advanced malignancy, such as melanoma, gastrointestinal tumor, esophageal cancer, et al. Although immune checkpoint blockade (ICB) treatment has been successful in different cancers, drug resistance and relapses are common，such as colorectal cancer. Therefore, it is necessary to improve the efficacy of immune checkpoint therapy for cancer patients who do not respond or lowly response to current treatments. N6-methyladenosine (m6A), as a key regulator of transcript expression, is the most frequently internal modification of mRNA in human body. Recently, it is proposed that m6A epigenetic modification is a potential driver of tumor drug resistance. In this review, we will briefly outline the relevant mechanisms, general treatment status of immune checkpoint inhibitors in colorectal cancer, how m6A epigenetic modifications regulate response of ICB in CRC and provide a new stratege for overcoming resistance of ICB in CRC.